1980
DOI: 10.1007/bf00428430
|View full text |Cite
|
Sign up to set email alerts
|

Secondary athrocytotic cardiomyopathy ? Heart damage due to Wilson's disease

Abstract: Post-mortem atomic absorption spectrophotometry of the myocardium of a 14-year-old boy revealed a hundred-fold increase in copper. Further electrolyte analysis of the myocardium showed changes corresponding to metabolic heart muscle damage. Ultrastructural examination showed all the feature of a cardiomyopathy at the cellular level. Laser-Microprobe-Mass-Analysis demonstrated an inhomogeneous distribution of copper. An essential factor in the mechanism of death is heart damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A recent report Kaduk et al [27] describing cardiomyopathy in Wilson's disease, suggested that mitochondrial alterations were the consequence of the accumulation of myocardial copper These alterations are non-specific, and in some cases of limited severity; however, in previous study it was concluded that cardiac degeneration might have contributed to the death of Wilson's patients [27] . PWD may well be associated with autonomic dysfunction in patients with Wilson's disease [27] . Dysautonomia, often subclinical, is only one of the many features of Wilson's disease [28] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report Kaduk et al [27] describing cardiomyopathy in Wilson's disease, suggested that mitochondrial alterations were the consequence of the accumulation of myocardial copper These alterations are non-specific, and in some cases of limited severity; however, in previous study it was concluded that cardiac degeneration might have contributed to the death of Wilson's patients [27] . PWD may well be associated with autonomic dysfunction in patients with Wilson's disease [27] . Dysautonomia, often subclinical, is only one of the many features of Wilson's disease [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Morphologic abnormalities and myocardial alterations consistent with cardiomyopathy have been previously reported in autopsy specimens of the hearts of Wilson disease patients (30). Myocardial damage and the presence of myocardial copper deposition 10-100 times the normal concentration have also been reported in the autopsy tissues of Wilson disease patients (4,39). However, conflicting results on the clinical impact of myocardial copper levels have been reported in previous studies (1,39,40).…”
Section: Wdmentioning
confidence: 95%
“…Myocardial damage and the presence of myocardial copper deposition 10-100 times the normal concentration have also been reported in the autopsy tissues of Wilson disease patients (4,39). However, conflicting results on the clinical impact of myocardial copper levels have been reported in previous studies (1,39,40). A limitation of our study is that we have no data on the copper levels in regional myocardial tissues and magnetic resonance imaging was not performed.…”
Section: Wdmentioning
confidence: 95%
See 2 more Smart Citations